2003
DOI: 10.1016/s1468-6996(02)00053-0
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic shielding behaviour of conducting polyaniline composites

Abstract: The paper reports the designing and development of conducting polyaniline composites which show a shielding effectiveness of 4 -58 dB against electromagnetic interference at 101 GHz range, depending upon the loading of the conducting polyaniline in polystyrene and polymethylmethaacrylate matrix. The composites can be used for the dissipation of static charge. A static decay time of the order of 0.11 -0.02 s for the conducting polyaniline composites is observed when the charge is reduced from 5000 to 500 V. q

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
108
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(111 citation statements)
references
References 28 publications
3
108
0
Order By: Relevance
“…Studies have shown that certain conducting polymers such as Polyaniline and Polypyrrole have been found to offer corrosion protection of iron, steel and aluminum, attributed to its high stability in the air, adhesion and redox properties with the substrate [5][6][7][8][9] . Amongst the class of conducting polymers, Polyaniline (PAni) is unique due to its easy synthesis, low cost, good thermal stability, and reversible doping/dedoping process to control the conductivity [10,11] . When reaction occurs in acidic environment (low pH condition), leads the head-to-tail coupling of aniline monomers in the para position and green form as a protonated emeraldine, which can be dedoped by oxidizing agent to produce the blue, emeraldine base form of the semi-conducting polymer [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that certain conducting polymers such as Polyaniline and Polypyrrole have been found to offer corrosion protection of iron, steel and aluminum, attributed to its high stability in the air, adhesion and redox properties with the substrate [5][6][7][8][9] . Amongst the class of conducting polymers, Polyaniline (PAni) is unique due to its easy synthesis, low cost, good thermal stability, and reversible doping/dedoping process to control the conductivity [10,11] . When reaction occurs in acidic environment (low pH condition), leads the head-to-tail coupling of aniline monomers in the para position and green form as a protonated emeraldine, which can be dedoped by oxidizing agent to produce the blue, emeraldine base form of the semi-conducting polymer [12][13][14] .…”
Section: Introductionmentioning
confidence: 99%
“…5 Among conducting polymers, polyaniline (PAni) and its analogues as micro/nanowires have been studied most extensively because their good environmental stability in both doped and undoped forms, low cost and ease of preparation, excellent physical and chemical properties, unique doping mechanism and its ease of protonic acid doping in the emeraldine form. 6,7 A series of up to date methods have been reported for synthesizing micro-/nanotubes of conducting polymers, such as template synthesis, electrospining, chiral nematic reaction and molecular beam deposition. 8,9 However, template free method is an excellent route to synthesize the micro/nanotubes of conducting polymers because the micelle consists of dopant or dopant/aniline salt could act as a ''soft template'' in the formation of the nanostructured PAni by omitting the using of ''hard template'' (e.g.…”
mentioning
confidence: 99%
“…[7][8][9] These composites of conducting polymer have prolonged their sphere and currently finding their application EMI shielding technology. 10 There is growing concern with respect to topics related to the environment. Coal-burning thermal power plants produce large amounts of flyash (FA) as a residue.…”
Section: Introductionmentioning
confidence: 99%